Antinociceptive activities of senduduk (Melastoma malabathricum L.) leaves methanolic extract and its petroleum ether fractions - Jaios, Erman Shah (2016)
Natural products that obtained from the extraction process of medicinal plants are being studied scientifically and endeavor to discover new potential therapeutic agents with less, or no side effect. Melastoma malabathricum L. is one of the medicinally important plants belonging to the family Melastomaceae, commonly known as “Senduduk” in Malay culture. Traditionally, leaves are claimed to relieve diverse pain-related ailments. Therefore, the objective of the present study was to examine the antinociceptive activities of M. malabathricum L. leaves methanolic extract (MEMM) and its petroleum ether (PEMM) fraction by using the in vivo models of nociception in both thermal- and chemical-induced pain tests. The dose of extracts (100, 250, and 500 mg/kg) was administered via orally 60 minutes (min) prior to subjection of the respective test in the volume of 10 mL/kg. Throughout this study, rats and mice (n=6) were pre-treated with the drugs or extract per group. The study was designed as a preventive method and the potential of MEMM and PEMM against nociception has never been reported. In the first stage, we were attempted to evaluate the extract antinociceptive activities, the in vivo thermal (hot plate test; HT), chemicals (acetic acid-induced abdominal constriction; ACT and formalin-induced paw licking test; FT) models of nociception were used. In order to elucidate the mechanisms of action involved, the role of opioid, vanilloid receptors (capsaicin), glutamate system (glutamatergic) and nitric-oxide/cyclic guanosine phosphate (NO/cGMP) pathway in modulation of the extract antinociceptive activities were determined. In the second stage, MEMM was partitioned into three fractions: petroleum ether (PEMM), ethyl acetate (EAMM), and aqueous (AQMM). Nevertheless, our objective in this second stage was to investigate the most potent fraction among the three extracts. Therefore, the experiment ED50 (effective dose producing a 50% reduction in relative to control value) and its 95% confidence intervals (CI) values were conducted to determine the most potent fraction and the ACT was used to screen the antinociceptive effect. From the calculation, PEMM is the most effective fraction was further used to assess the antinociceptive properties using the in vivo models of nociception. Moreover, all the extracts (MEMM, PEMM, EAMM and AQMM) underwent the phytochemical screening such as Flavanoids Test, Saponins Test, Tannins and Polyphenolic Compounds Test, Steroids / Triterpenes Test, and Alkaloids Test were recorded. Analysis and identification of phytochemical constituents with the aid of High-Performance Liquid Chromatography (HPLC) and Gas Chromatography (GC-MS) technique were performed. In the first stage, MEMM significantly (P < 0.05) was exhibited antinociceptive activities in all the chemically- and thermally-induced nociception models. Naloxone (5 mg/kg), a non-selective opioid antagonist, significantly (P < 0.05) was failed to affect the antinociceptive activity of MEMM. Moreover, MEMM antinociception significantly (P < 0.05) was reversed the capsaicin- and glutamateinduced paw licking test. Whereas, L-arginine (a nitric oxide precursor), L-NAME (an inhibitor of NO synthase), methylene blue, MB (an inhibitor of cGMP), or their combination significantly (P < 0.05) was failed to change the intensity of MEMM antinociception. In the second stage, it was shown the verified screening of the antinociceptive effect of PEMM, EAMM and AQMM fractions assessed by ACT. Likewise, the PEMM and EAMM had similar efficacy to produce antinociceptive effect [max. inhibitions of 24.17±1.33 (70.94%) and 18.83±0.91 (77.36%)] at the dose 500 mg/kg, respectively. As a result, the PEMM was more effective than the EAMM with the calculation of ED50 values [with 95% confidence interval (C.I)] of 119.5 mg/kg (97.03 – 147.1 mg/kg) and 125.9 mg/kg (109.9 – 144.1 mg/kg), respectively. PEMM significantly (P < 0.05) was exhibited antinociceptive activity in all the chemically- and thermally-induced nociception models. Naloxone (5 mg/kg), a non-selective opioid antagonist, significantly (P < 0.05) was failed to reverse the antinociceptive effect of PEMM assessed using the HT and FT. PEMM antinociception significantly (P < 0.05) was reversed the capsaicin- and glutamateinduced paw licking test. Furthermore, L-arginine, L-NAME, MB, or their combination significantly (P < 0.05) was also failed to interfere the PEMM antinociception effect. The phytochemical analysis was screened for all the extracts, and presence of flavonoids, tannins, saponins, triterpenes and steroids, but no alkaloids. In addition, the HPLC analysis of MEMM and PEMM were demonstrated the presence of flavonoids as its major constituents. In the GC-MS analysis, the phytoconstituents were screened and majority of these identified compounds are palmitic acid, terpene, diterpene, -Linolenic acid and fatty acid ester. Together, these results indicate that the MEMM produced dose-dependent antinociception in the in vivo nociception models of chemical and thermal with the aids of the phytoconstituents, whereby, the PEMM was considered to have the best activity of antinociceptive activities among the fractions, which warrants further investigation.